2015
DOI: 10.1074/jbc.m115.655175
|View full text |Cite
|
Sign up to set email alerts
|

Two Isoforms of the RNA Binding Protein, Coding Region Determinant-binding Protein (CRD-BP/IGF2BP1), Are Expressed in Breast Epithelium and Support Clonogenic Growth of Breast Tumor Cells

Abstract: Background:The RNA binding protein, coding region determinant-binding protein (CRD-BP), is expressed by tumor cells and protects key mRNAs. Results: This study identifies a novel variant of CRD-BP and finds that CRD-BP is required for breast tumor cell clonogenicity. Conclusion: CRD-BP has tumorigenic activity and is ubiquitously expressed in breast epithelium. Significance: Under-reporting of CRD-BP isoforms suggests that published studies may be incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 52 publications
0
58
0
Order By: Relevance
“…While it has been appreciated that mRNA-binding proteins including IMP1, Lin28b, and Musashi are increased in epithelial tumor cells, it is not yet known if these factors play a role in the tumor microenvironment (1013). Imp1- hypomorphic mice exhibit dwarfism, decreased organ size, morphologically defective intestines, and death near birth for a large portion of mice (14, 15). Recent studies demonstrated a specific role for IMP1 to promote expansion of fetal neural stem cells via post-transcriptional enhancement of self-renewal gene products including Hmga2 (16).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been appreciated that mRNA-binding proteins including IMP1, Lin28b, and Musashi are increased in epithelial tumor cells, it is not yet known if these factors play a role in the tumor microenvironment (1013). Imp1- hypomorphic mice exhibit dwarfism, decreased organ size, morphologically defective intestines, and death near birth for a large portion of mice (14, 15). Recent studies demonstrated a specific role for IMP1 to promote expansion of fetal neural stem cells via post-transcriptional enhancement of self-renewal gene products including Hmga2 (16).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GHET1 have been shown to directly interact with insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1) and have increased the physical interface between MYC mRNA and IGF2BP1 (18). Considering the role of GHET1 in regulation of MYC mRNA stability and expression via its interaction with IGF2BP1 (18), frequent MYC dysregulation in breast cancer (20) as well as expression of IGF2BP1 in breast cancer and its role in clonogenic growth of these cells (21), GHET1 was expected to participate in breast cancer pathogenesis as well. However, the results of the present study showed no consistent expression trend in samples with breast cancer examined.…”
Section: Discussionmentioning
confidence: 99%
“…Imp1 hypomorphic mice exhibit intestinal defects and perinatal lethality, yet the contribution of IMP1 to normal gut homeostasis and repair is not known (Fakhraldeen et al, 2015, Hansen et al, 2004. We utilized CRISPRmediated IMP1 deletion in the SW480 colorectal cancer cell line to evaluate "translatome"-wide effects of IMP1 loss ( Fig.…”
Section: Imp1 Knockout Reveals Global Changes In Active Translationmentioning
confidence: 99%
“…Evidence in Imp1 hypomorphic mice, which express only 20% of wild type Imp1, suggests that its expression is critical for normal growth and development, as these mice exhibit high perinatal mortality and morphological defects in intestine epithelium (Fakhraldeen et al, 2015, Hansen et al, 2004. We therefore evaluated VillinCre; Imp1 fl/fl mice (Imp1 ΔIEC mice), in which IMP1 is deleted solely in intestinal and colonic epithelium (Hamilton et al, 2013).…”
Section: Mice With Imp1 Loss Exhibit Morphological Changes In Paneth mentioning
confidence: 99%
See 1 more Smart Citation